Building positive resilience through vulnerability analysis. Issue 4 (27th June 2020) - Kubacki, Krzysztof; Siemieniako, Dariusz; Brennan, Linda
Abstract : Purpose: The purpose of this paper is to propose an integrative framework for vulnerability analysis in social marketing systems by identifying, investigating and problematising the relationships among several interrelated concepts, including power, power asymmetry, vulnerability and resilience, in the context of social marketing systems. Design/methodology/approach: This is a conceptual paper synthesising literature from social marketing, sociology and marketing management. Findings: The main outcome of the discussion is a proposed integrative framework for vulnerability analysis. The framework identifies the main groups of stakeholders within a social marketing system and the bases for their power and consequential power asymmetries. It focusses on the types and states of vulnerability to identify the distinct characteristics of the social conditions of vulnerability for micro-level system actors. It leads to building positive resilience through efforts aiming to change the power asymmetries at the downstream, midstream and upstream levels. Originality/value: The integrative framework for vulnerability analysis answers the call from Wood (2019 ) for the development of practical approaches to better understand resilience-building approaches in social marketing programmes. The framework provides reconciliation for diverse dimensions of vulnerability as a natural characteristic of all social marketing systems and as a universal, constant and inherent social condition.